Meta-rectenna array for electromagnetic energy harvesting - Emanoil Surducan; Vasile Surducan; Robert Gutt (Results in Engineering, 2025)
This paper proposes the integration of a specially designed metamaterial substrate with an ultra-wideband (UWB) antenna to form a highly efficient meta-rectenna array for electromagnetic (EM) energy harvesting across a broad frequency range (800 MHz to 3 GHz), encompassing all major RF communication bands. A patented, custom-designed UWB antenna is employed alongside a metamaterial substrate composed of a microstrip structure featuring a logarithmic copper spiral. The spiral metamaterial is analyzed both individually as an antenna element operating near 1 GHz and as part of a multi-unit array to characterize its reflection (S11) and transmission (S12) properties. Notably, the metamaterials enhance coupling below 1 GHz when compared to a conventional reference rectenna. The combined metamaterial-antenna system (meta-antenna) is experimentally characterized using transmission measurements, where the metamaterial's impact is clearly observed in the sub-1 GHz range. Employing a rectifying circuit, the resulting meta-rectenna array, consisting of four serially connected rectennas, is tested for EM harvesting potential from 500 MHz to 3 GHz. The system demonstrates significant energy harvesting performance in frequency regions where the reference rectenna remains inactive. Without requiring any antenna redesign, the use of metamaterials leads to a 60× increase in harvested power at key resonant frequencies, showcasing the effectiveness of combining spiral metamaterials with a UWB antenna in next-generation wireless power and energy harvesting applications.